Reflections on Irish industrial policy towards foreign direct investment - Holger Görg; Frances P. Ruane (Trinity College, Department of Economics, 1997)
Irish policy towards foreign direct investment has evolved since the 1950s as a strategy driven primarily by the use of fiscal incentives to enhance the profitability of locating in Ireland, with grants as required to achieve a particular bargaining advantage in competing against alternative international locations. Our empirical analysis of European firms in Ireland suggests that the investment incentives offered appear to have led to significant gross job gains in the targeted high-tech sectors, as proxied here by the Metals & Engineering and Chemicals sectors. However, these gross gains have not translated into net gains of a similar magnitude.
Keywords: F23; L6; 330; Industriepolitik; Direktinvestition; Beschäftigung; Irland; Welt